The Immunomodulatory Effect of You-Gui-Wan on Dermatogoides-pteronyssinus-Induced Asthma. (20th May 2012) - Lin, Li-Jen; Lin, Chin-Che; Wang, Shulhn-Der; Chao, Yun-Peng; Kao, Shung-Te
Abstract : The traditional Chinese medicine You-Gui-Wan (YGW) contains ten species of medicinal plants and has been used to improve health in remissive states of asthma for hundreds of years in Asia. However, little is known about the immunomodulatory mechanisms in vivo. Therefore, this study investigated the pathologic and immunologic responses to YGW in mice that had been repeatedly exposed to Dermatogoides-pteronyssinus (Der p). YGW reduced Der-p-induced airway hyperresponsiveness and total IgE in serum. It also inhibited eosinophil infiltration by downregulating the protein expression of IL-5 in serum and changed the Th2-bios in BALF by upregulating IL-12. Results of the collagen assay and histopathologic examination showed that YGW reduced airway remodeling in the lung. In addition, after YGW treatment there was a relative decrease in mRNA expression of TGF- β 1, IL-13, eotaxin, RANTES, and MCP-1 in lung in the YGW group. The results of EMSA and immunohistochemistry revealed that YGW inhibited NF- κ B expression in epithelial lung cells. YGW exerts its regulative effects in chronic allergic asthmatic mice via its anti-inflammatory activity and by inhibiting the progression of airway remodeling.